Subject Matter Competence of Arbitration Court in Respect to Cases of Legal Norm Acts Challenge : Walking in Circulation - V. B. Nemtseva (Сибирское юридическое обозрение, 2013)
The article presents the review of the ways determining the cases of legal norm acts challenge considered by arbitration court, their merits and demerits.